Ferroelectric Phase Content in 7 nm Hf(1−x)ZrxO2 Thin Films Determined by X‐Ray‐Based Methods. Issue 10 (18th April 2021) - Mukundan, Vineetha; Consiglio, Steven; Triyoso, Dina H.; Tapily, Kandabara; McBriarty, Martin E.; Schujman, Sandra; Beckmann, Karsten; Hazra, Jubin; Kaushik, Vidya; Cady, Nathaniel; Clark, Robert D.; Leusink, Gert J.; et al.
Abstract : The recent discovery of ferroelectric behavior in hafnia‐based dielectrics attributed to the formation of noncentrosymmetric orthorhombic phase has opened up potential uses in numerous applications ranging from ferroelectric field effect transistors to pyroelectric energy harvesters. Herein, the relative amounts of ferroelectric orthorhombic phase (space group Pca21 ) in 7 nm‐thick hafnia–zirconia (HZO) films of three compositions (Hf0.2 Zr0.8 O2, Hf0.5 Zr0.5 O2, and Hf0.8 Zr0.2 O2 ) are reported. The ferroelectric behavior in these ultrathin HZO films prepared by atomic layer deposition (ALD) in metal–insulator–metal (MIM) stacks is verified by polarization measurements. Using grazing incidence X‐ray diffraction (GIXRD) and grazing incidence‐extended X‐ray absorption fine structure spectroscopy (GI‐EXAFS), the relative phase percentages of three key phases (monoclinic—P21 /c, orthorhombic—Pca21, and tetragonal—P42 /nmc) are assessed. Among these compositions, Hf0.5 Zr0.5 O2 is determined to have the highest amount of the ferroelectric phase. The monoclinic phase is found to be dominant for Hf0.8 Zr0.2 O2, whereas the tetragonal phase is found to be dominant for Hf0.2 Zr0.8 O2 . Independent GI‐EXAFS measurements of Hf and Zr suggest that there is no significant segregation of either oxide into a particular crystal phase. Strong agreement between the measurement methods reveals the structure–property function correlation in these ultrathin hafnia–zirconia films with greater certainty than previously achieved. Abstract : Herein, the crystal phase distribution in ultrathin hafnia–zirconia films prepared by atomic layer deposition as metal–insulator–metal stacks using X‐ray diffraction and extended X‐ray absorption fine structure spectroscopy is analyzed. Ferroelectric nature in these stacks is confirmed by polarization measurements.